Isle of Man : Crown Dependency of the United Kingdom; Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
The financial regulatory and supervisory system of the Isle of Man complies well with the assessed international standards. Volume I of this report provides an overview and summary findings. Volume II provides the detailed findings of the assessments of compliance with the Basel Core Principles for Effective Banking Supervision (BCP); the Insurance Core Principles of the International Association of Insurance Supervisors (IAIS); and the Objectives and Principles of Securities Regulation of the International Organization of Securities Commissions (IOSCO).